The impact of household wealth status on anxiety and depression of Nepal reproductive age women: Propensity score matching analysis - Angwach Abrham Asnake; Bezawit Melak Fente; Beminate Lemma Seifu; Hiwot Altaye Asebe; Mamaru Melkam; Meklit Melaku Bezie; Yohannes Mekuria Negussie; Zufan Alamrie Asmare (Heliyon)
Background: Mental health problems, particularly anxiety and depression, are indeed among the leading health challenges worldwide, affecting individuals across all age groups and geographic locations. The relationship between mental health and socioeconomic factors, including household wealth status, is well-documented. However, there are currently no studies demonstrating a causal relationship between household wealth and common mental disorders, such as anxiety and depression. Therefore, this study aimed to assess the effect of household wealth status on anxiety and depression through Propensity Score Matching analysis (PSM) analysis. Methods: This study used the recent 2022 Nepal Demographic and Health Survey (NDHS). A weighted sample of 7411 reproductive-age (aged 15–49 years) women who were interviewed for mental health conditions were included in this study. Anxiety and depression were the dependent variables of this study. The NDHS utilized the Generalized Anxiety Disorder 7-item scale (GAD-7) to assess levels of anxiety among participants and the Patient Health Questionnaire 9 (PHQ-9) to evaluate depression. PSM analysis was employed to examine the causal connection between household wealth and women's anxiety and depression by controlling for confounding variables. Results: The average treatment effects (ATE) of non-poor household status on anxiety and depression were −0.015 and −0.052 respectively, indicating that non-poor household status reduces women's anxiety and depression. It implies the difference in risks of anxiety and depression that would be observed if everyone in the population were from non-poor households, versus if everyone in the population were from poor households were 1.5 % and 5.2 % respectively. The average treatment effect on treated (ATT) result showed that women from non-poor wealth status households reduced the risk of anxiety and depression by 1.1 % and 9.2 % respectively among treated groups. Conclusion: This study evidenced that causal relationship between household wealth status and common mental health conditions as such anxiety and depression. This suggests, it is better to focus on improving the wealth status of households to enhance the mental health of reproductive-age women. By understanding the multidimensional aspects of poverty and their links to mental health, stakeholders can create more effective strategies to support affected individuals and communities. This can contribute to breaking the cycle of poverty and improving overall well-being.